The study of unclassified B[e] stars and candidates in the Galaxy and Magellanic Clouds†. Issue 1 (6th June 2019) - Condori, C A H; Borges Fernandes, M; Kraus, M; Panoglou, D; Guerrero, C A
ABSTRACT: We investigated 12 unclassified B[e] stars or candidates, 8 from the Galaxy, 2 from the Large Magellanic Cloud (LMC), and 2 from the Small Magellanic Cloud (SMC). Based on the analysis of high-resolution spectroscopic (FEROS) and photometric data, we confirmed the presence of the B[e] phenomenon for all objects of our sample, except for one (IRAS 07455-3143). We derived their effective temperature, spectral type, luminosity class, interstellar extinction and, using the distances from Gaia DR2, we obtained their bolometric magnitude, luminosity, and radius. Modelling of the forbidden lines present in the FEROS spectra revealed information about the kinematics and geometry of the circumstellar medium of these objects. In addition, we analysed the light curves of four stars, finding their most probable periods. The evolutionary stage of 11 stars of our sample is suggested from their position on the HR diagram, taking into account evolutionary tracks of stars with solar, LMC, and SMC metallicities. As results, we identified B and B[e] supergiants, B[e] stars probably at the main sequence or close to its end, post-AGB and HAeB[e] candidates, and A[e] stars in the main sequence or in the pre-main sequence. However, our most remarkable results are the identification of the third A[e] supergiant (ARDB 54, the first one in the LMC), and of an 'LBV impostor' in the SMC (LHA 115-N82).